Research of device for air distribution with swirl and spread air jets at variable mode - Возняк, Орест Тарасович; Сухолова, Ірина Євгенівна; Миронюк, Христина Володимирівна (Eastern-European Journal of Enterprise Technologies, 2015)
The research deals with solving the urgent problem of improving the efficiency of air distribution with the swirl and spread air jets to ensure regulatory parameters of the air in industrial premises. The mathematical model of air supply with the swirl and spread air jets in these premises is improved. It is shown that for maximum air distribution efficiency, air should be supplied with the jets that are intensively damped before entering the working area. The design of the air distributor with the formation of swirl and spread air jets, providing intense damping of the velocity and excess temperature of the resulting air flow is developed and investigated. The feature of this design is the ability to feed two supply air jets, the swirl air jet, formed after having passed through plates, and the spread air jet, which comes from the annular slot. This ensures intense mixing of supply air jets of the ambient air and provides the variable mode. Graphic dependencies are built, and theoretical dependencies are derived based on experimental studies that can be used in further engineering computations. The designs of air distributors for air supply with swirl and spread air jets and feeding the supply air jets in the variable mode are developed and protected by patents Ukraine. The economic efficiency of double-jet air distributors compared to the alternatives is shown, specific performance of air distribution is presented.